Modest effect on plaque progression and vasodilatory function in atherosclerosis-prone mice exposed to nanosized TiO2 - Mikkelsen Lone; Sheykhzade Majid; Jensen Keld A; Saber Anne T; Jacobsen Nicklas R; Vogel Ulla; Wallin Håkan; Loft Steffen; Møller Peter (Particle and Fibre Toxicology, 2011)
Abstract Background There is growing evidence that exposure to small size particulate matter increases the risk of developing cardiovascular disease. Methods We investigated plaque progression and vasodilatory function in apolipoprotein E knockout (ApoE-/-) mice exposed to TiO2. ApoE-/- mice were intratracheally instilled (0.5 mg/kg bodyweight) with rutile fine TiO2 (fTiO2, 288 nm), photocatalytic 92/8 anatase/rutile TiO2 (pTiO2, 12 nm), or rutile nano TiO2 (nTiO2, 21.6 nm) at 26 and 2 hours before measurement of vasodilatory function in aorta segments mounted in myographs. The progression of atherosclerotic plaques in aorta was assessed in mice exposed to nanosized TiO2 (0.5 mg/kg bodyweight) once a week for 4 weeks. We measured mRNA levels of Mcp-1, Mip-2, Vcam-1, Icam-1 and Vegf in lung tissue to assess pulmonary inflammation and vascular function. TiO2-induced alterations in nitric oxide (NO) production were assessed in human umbilical vein endothelial cells (HUVECs). Results The exposure to nTiO2 was associated with a modest increase in plaque progression in aorta, whereas there were unaltered vasodilatory function and expression levels of Mcp-1, Mip-2, Vcam-1, Icam-1 and Vegf in lung tissue. The ApoE-/- mice exposed to fine and photocatalytic TiO2 had unaltered vasodilatory function and lung tissue inflammatory gene expression. The unaltered NO-dependent vasodilatory function was supported by observations in HUVECs where the NO production was only increased by exposure to nTiO2. Conclusion Repeated exposure to nanosized TiO2 particles was associated with modest plaque progression in ApoE-/- mice. There were no associations between the pulmonary TiO2 exposure and inflammation or vasodilatory dysfunction.